Fabrication and characterization of diamond-like carbon coated knife edge field emitter array - Ko, CG; Ju, BK; Lee, YH; Park, JH; Oh, MH (JAPAN SOC APPLIED PHYSICS, 1996)
We fabricated diamond-like carbon (DLC) coated knife edge-shaped field emitter array (KEFEA) on the (110) silicon wafer. The fabricated KEFEA has more than six hundreds times of aspect ratio and about two times higher electric field at tip-apex compared with the pyramid-shaped edge field emitter array (FEA). A high quality DLC film which has similar properties to the diamond film was coated on the silicon KEFEA by PECVD method in order to improve the stability and electrical characteristics. The turn-on held was lowered from 0.18 MV/cm to 0.14 MV/cm by the DLC him coating to the pure silicon KEFEA. More than 400% of the short-term emitted current fluctuation was observed from the measurement of the pure silicon KEFEA; The DLC film coating on the pure silicon KEFEA reduced the emission current fluctuation to 15%.
Keywords: SILICON